Plants of Quetico and the Ontario shield - Walshe, Shan, 1935- (Heritage., 1980)
A handy guide, with more than 200 colour illustrations, to the plants, shrubs, and trees of Quetico Provincial Park which will be of use far beyond its borders. It includes notes on the abundance, habitat, and distribution of species.